Beyond CAPM: an innovative factor model to optimize the risk and return trade-off - Lashgari, Shima; Antuchevičienė, Jurgita; Delavari, Alireza; Kheirkhah, Omid (Journal of Business Economics and Management, 2014)
Different models have tried to improve the Capital Asset Pricing Model findings, on the basis that different factors can affect asset return. This paper examines a series of explanatory factors, broader than those explained by traditional theory, to see whether they are able to more accurately explain the returns. Should the previous point be confirmed, we must consider that the risk of an asset depends on multiple factors, rather than the few that are usually identified in the literature. Even though more than 300,000 factors are examined in this paper, the results show that in recent years just 87 factors are able to fully explain the returns of 4,500 companies in the 15 European countries examined. Our analysis also shows that business and macroeconomic, rather than financial factors, are those that heavily bear on asset returns; and that factors that affect asset return, either only positively or only negatively, do not exist. However, the same factor can affect some companies positively and others negatively. Thus, since not all firms are always sensitive to the same factors, there is the possibility to further decrease risk in proportion to return, through a factor-based risk optimisation process.First published online: 23 Sep 2013